CSF1R-related disorder: historical overview & current concepts - Wszolek, Zbigniew (Henry Stewart Talks, 2024)
Hereditary diffuse leukoencephalopathy, Colony stimulating factor 1 receptor (CSF1R), CSF1R-related leukoencephalopathy, Treatment for CSF1R-related leukoencephalopathy, Bone marrow transplant & experimental therapies for CSF1R-related disorder